CITIZENSHIP AND ENTREPRENEURIAL HUMAN CAPITAL IN UNFV STUDENTS - TASAYCO-ARANA, Dolores (2024)
The objective of this research is to know the expectations and perceptions of UNFV students, in relation to the topics that are current in the debate of the current political situation: the questioning of the effectiveness of representative democracy in the last 30 years and also the paradigm of the private business management system that despite its relative success in multiplying GDP up to 5 times, has failed to universalize the market economy, decentralization and productive diversification, decent employment, productivity and competitiveness in the external markets. For this purpose, the 2023 enrollees have been selected from three of the UNFV Faculties: Economics, Civil Engineering and Sociology, which are representative of business sciences, engineering and social sciences respectively. To find an explanation for these perceptions and attitudes, variables from the students' family have been addressed, such as the geographical origin of the parents, family income, social differentiation taking into account the Socio-Economic Levels of belonging and geographical mobility. Results: The student is sensitive to pointing out as a precondition for the functioning of liberal democracy, the validity of the so-called economic democracy, which consists of giving citizens equal opportunities not only for their business training, but also access to property. of raw materials, credit, innovation and natural resources for their use and massive creation of productive jobs. An important conclusion is the assessment of the training action of the UNFV, in relation to private business development, future employment, towards which the majority of students of the investigated specialties are inclined.